2009
DOI: 10.1007/s00127-009-0498-2
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of care in patients discharged from acute psychiatric inpatient facilities

Abstract: This study provides information on the characteristics and the pattern of care of patients discharged from inpatient facilities in a country that has closed down all its mental hospitals. This information may be relevant for those countries that are affording now the downsizing of MHs, and the expansion of community-based models of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 52 publications
6
18
0
1
Order By: Relevance
“…As observed in other surveys [8,37], approximately one-third of patients did not participate in RF chores. In terms of institutional support/rehabilitation, most RF activities concerned facility management, and few were targeted at integrating patients within the local community.…”
Section: Residents' Clinical Features and Activity Levelssupporting
confidence: 67%
“…As observed in other surveys [8,37], approximately one-third of patients did not participate in RF chores. In terms of institutional support/rehabilitation, most RF activities concerned facility management, and few were targeted at integrating patients within the local community.…”
Section: Residents' Clinical Features and Activity Levelssupporting
confidence: 67%
“…As a positive treatment response is usually defined in the literature as greater than 20% reduction in BPRS (Lachar et al, 1999), our findings showed that a short LOS in our ward was highly effective. Our results are consistent with previous systematic reviews (Alwan et al, 2008;Johnstone and Zolese, 2009) and the two Italian surveys (Ballerini et al, 2007a(Ballerini et al, , 2007bBarbato et al, 2010;Preti et al, 2009), suggesting that a short hospitalization is sufficient for the majority of patients (Frieri et al, 2013).…”
Section: Discussionsupporting
confidence: 95%
“…In Italy, patient characteristics differ between private and public (psychiatric) hospitals. Older patients are less likely to be unemployed and make more use of private services …”
Section: Resultsmentioning
confidence: 99%